2003
DOI: 10.1080/0959523021000059811
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in outcomes for men and women after drug misuse treatment: results from the National Treatment Outcome Research Study (NTORS)

Abstract: The National Treatment Outcome Research Study (NTORS) is a prospective, multi-site treatment outcome study of drug misusers in the UK. This paper reports the characteristics and problems of male and female clients at intake to treatment, and changes in substance use, health problems, and criminal behaviour at follow-up. The sample comprised 753 subjects (552 men and 201 women) followed-up 1 year after starting treatment in 54 programmes chosen to be representative of the main national treatment modalities. Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…Research from a national treatment outcome study showed that drug treatment use among men was associated with stronger family opposition to their drug use and more support for treatment, whereas for women it was associated with more mental health problems and self-referral into treatment (Grella and Joshi 1999). Past research has also shown that women tend to enter treatment after fewer years of use but that they present to treatment with a more severe clinical profile and more problems related to mental health, family and interpersonal relationships, employment, and physical health (Grella, Scott et al 2003;McKay et al 2003;Stewart et al 2003;Wechsberg, Craddock, and Hubbard 1998).…”
Section: Gender Differences In Drug Use and Treatment Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from a national treatment outcome study showed that drug treatment use among men was associated with stronger family opposition to their drug use and more support for treatment, whereas for women it was associated with more mental health problems and self-referral into treatment (Grella and Joshi 1999). Past research has also shown that women tend to enter treatment after fewer years of use but that they present to treatment with a more severe clinical profile and more problems related to mental health, family and interpersonal relationships, employment, and physical health (Grella, Scott et al 2003;McKay et al 2003;Stewart et al 2003;Wechsberg, Craddock, and Hubbard 1998).…”
Section: Gender Differences In Drug Use and Treatment Participationmentioning
confidence: 99%
“…Research from a national treatment outcome study showed that drug treatment use among men was associated with stronger family opposition to their drug use and more support for treatment, whereas for women it was associated with more mental health problems and self-referral into treatment (Grella and Joshi 1999). Past research has also shown that women tend to enter treatment after fewer years of use but that they present to treatment with a more severe clinical profile and more problems related to mental health, family and interpersonal relationships, employment, and physical health (Grella, Scott et al 2003;McKay et al 2003;Stewart et al 2003;Wechsberg, Craddock, and Hubbard 1998).Third, treatment processes, retention, completion, and outcomes appear to be influenced by gender (Green 2006;Grella, Scott, and Foss 2005). Among patients treated in an HMO setting, Green, Polen, Dickinson, Lynch, and Bennett (2002) found that although time in treatment and rates of treatment completion did not differ by gender, different participant characteristics were related to retention and completion for males and females.…”
mentioning
confidence: 99%
“…The results offer some suggestions that there may be a possible gender difference, with slightly (but not significantly) higher rates of volatile substance abuse among the young women in our sample. In general, young women report lower prevalence for use of many substances, but those females who do use illicit substances often have more severe difficulties relating to their substance use (Stewart et al, 2003). While more research is required to assess the relative impact of volatile substance abuse by gender, the slightly higher rate of volatile substance abuse in girls may be associated with this elevated level of other lifestyle problems reported in the results.…”
Section: Discussionmentioning
confidence: 77%
“…However, there were no significant gender differences in terms of crime reduction. Stewart, Gossop, Marsden, Kidd, and Treacy (2003) concluded that gender was not predictive of any outcome measures and that both men and women made significant improvements in their problem behaviors. Alterman, Randall, and McLellan (2000) also found no significant gender differences in alcohol or drug outcomes at 7-month follow-up of nine community treatment programs.…”
Section: Gender Differences In Drug Misuse Among Arrestees 903mentioning
confidence: 98%